MANAGEMENT OF THE INTEGRATED ISLAMIC SCIENCE-BASED CURRICULUM AT NONFORMAL EDUCATION: A CASE STUDY OF ABATA MOVEMENT INDONESIA - Annafi, Novia; Choiriyah, Siti (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
ABSTRACT Science-based curriculum integrated with Islamic values ??continues to be carried out based on the development of the times and the spirit of ijtihad or innovation in overcoming complex life problems in the 21st century era. This study aims to analyze the planning and implementation of the science curriculum management  based on Islamic values. This study uses a qualitative method with a case study approach. The instruments used were interviews with the coordinator of the foundation's program team and teachers, observations by observing and participating in the process of implementing curriculum innovation Abata Sains Quran at the non-formal educational institution Abata Movement Indonesia, and studies of existing research literature on educational institutions, both formal and non-formal, in implementing science-based curriculum innovation, especially in order to form a STEAM learning system (Science, Technology, Engineering, Art, and Mathematics) in Abata Sains Quran Program (ASIQ). The data were analyzed using qualitative analysis techniques by Milles and Huberman on the concept of the program that has been implemented. The result indicated that the ASIQ (Abata Sains Quran) program at Yayasan Abata Movement Indonesia was planned by the Manager Program through compiling the blueprint and socializing to the stakes holders such as teachers and volunteers who were involved in this program. Challenges and supporting factors are also faced by Manager Program such as contextualization of various terms in science which are suitable for children. ABSTRAK Kurikulum berbasis sains yang terintegrasi dengan nilai-nilai Islam terus berkembang seiring perkembangan zaman dan semangat ijtihad atau inovasi dalam menghadapi permasalahan kehidupan yang kompleks di era abad ke-21. Penelitian ini bertujuan untuk menganalisis perencanaan dan implementasi manajemen kurikulum sains yang berlandaskan nilai-nilai Islam. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Instrumen yang digunakan meliputi wawancara dengan tim koordinator program yayasan dan para guru, observasi dengan mengamati serta berpartisipasi dalam proses pelaksanaan inovasi Abata Sains Quran di lembaga pendidikan nonformal Abata Movement Indonesia, serta kajian literatur terhadap penelitian-penelitian yang telah ada pada lembaga pendidikan formal dan nonformal terkait penerapan inovasi kurikulum berbasis sains, khususnya dalam pembentukan sistem pembelajaran STEAM (Science, Technology, Engineering, Art, and Mathematics) dalam Program Abata Sains Quran (ASIQ). Data dianalisis menggunakan teknik analisis kualitatif Miles dan Huberman pada konsep program yang telah dilaksanakan. Hasil penelitian menunjukkan bahwa Program ASIQ (Abata Sains Quran) di Yayasan Abata Movement Indonesia direncanakan oleh Manajer Program melalui penyusunan cetak biru dan sosialisasi kepada para pemangku kepentingan seperti guru dan relawan yang terlibat dalam program ini. Berbagai tantangan dan faktor pendukung juga dihadapi oleh Manajer Program, seperti kebutuhan untuk mengkontekstualisasikan berbagai istilah dalam sains agar sesuai dengan pemahaman anak-anak.